Amelioratory Effect of Resistant Starch on Non-alcoholic Fatty Liver Disease via the Gut-Liver Axis - Zhu, Weifeng; Zhou, Ying; Tsao, Rong; Dong, Huanhuan; Zhang, Hua (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a hepatic manifestation of metabolic syndrome that has reached a global prevalence. The impaired gut barrier function caused by unhealthy diet plays a key role in disrupting the immune-metabolic homeostasis of the gut-liver axis (GLA), leading to NAFLD. Dietary interventions have therefore been studied as a feasible alternative therapeutic approach to ameliorating NAFLD. Resistant starches (RSs) are characterized as prebiotics contributing to reduced systemic inflammation in patients with metabolic syndrome. The present review aims to elucidate the mechanisms of the GLA in alleviating NAFLD, and to provide insights into how dietary RSs counteract diet-induced inflammation in the GLA. Emerging evidence suggests that the intake of RSs alter gut microbiota structure, enhances mucosal immune tolerance and promotes the production of microbial metabolites such as short-chain fatty acids (SCFAs) and secondary bile acids (BSs). These metabolites not only directly stimulate the growth of intestinal epithelial cells, but more importantly elicit GPR41/GPR43, FXR, and TGR5 signaling cascades to sustain the immune-metabolic homeostasis in GLA. The literature also revealed the dietary-immune-metabolic interplay by which RSs exert their regulatory effect on the immune-metabolic crosstalk of GLA and the related molecular basis, suggesting that dietary intervention with RSs may be a promising alternative therapeutic strategy against diet-induced dysfunction of GLA, and ultimately the risk of developing NAFLD.